Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
Table of Content: 1. The degree to which school principals practice transformational leadership and its relationship to the level of risk and emergency management in schools in The Sultanate of Oman Mr. Ali Hamad Al-Buraiki ,Dr. Youssef Nait Belaid 2. The role of the school principal in professional development from the point of view of intermediate science and mathematics teachers in Riyadh Ms. May Abdulaziz Al Abdulsalam, Dr. Saham Mohammed Kaaki 3. Adaptive leadership among school principals and its relationship to the teaching self-efficacy of intermediate school teachers in public schools in Mecca from the point of view of educational supervisors Ms. Salha Muhammad Abudahi 4. The Factor Analysis and psychometric characteristics of the self-motivation scaling and the Self-Efficacy scale of the sample of the school students in the Sultanate of Oman Dr. Saif Darwish Alharrasi 5. Psychological Resilience and Its Relationship with Rumor Perception in Electronic Social Media Among Women in Al-Madinah Al-Munawwarah Ms. Amal Atiyat Allah Al-Mohammadi 6. Intellectual stress as a predictor of Type D personality among a sample of graduate students at King Abdulaziz University in Jeddah Ms. Esraa Saad Alomari, Dr. Fatma Khalifa Elsayed 7. Future scenarios for electronic training in Saudi universities Ms. Tahani Ayed Alruhaimi, Ms. Manal Trekhem Alharthi, Ms. Noura Ibrahim Almohanna, Dr. Fatemah Abdalaziz Altuwaijri 8. Evaluating the practices of student teachers in teaching mathematics in resource rooms in Jordan Co-Prof. Mohammad A. Beirat, Co-Prof. Hisham A. Almakanin, Co-Prof. Zaidan Alkhamaiseh